2008
DOI: 10.2337/dc07-2105
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Tolerability of Pregabalin Treatment for Painful Diabetic Peripheral Neuropathy

Abstract: EDITH DURSO-DECRUZ, PHD 2 BIROL EMIR, PHD 2 OBJECTIVE -To evaluate the efficacy, safety, and tolerability of pregabalin across the effective dosing range, to determine differences in the efficacy of three times daily (TID) versus twice daily (BID) dosage schedules, and to use time-to-event analysis to determine the time to onset of a sustained therapeutic effect using data from seven trials of pregabalin in painful diabetic peripheral neuropathy (DPN).RESEARCH DESIGN AND METHODS -Data were pooled across seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
178
1
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(204 citation statements)
references
References 25 publications
6
178
1
12
Order By: Relevance
“…Treatment-emergent peripheral edema was reported in 13.4% of pregabalin-treated patients in this study, which is similar to the incidence reported in the previous trial of pregabalin for SCI (10%) 14 and comparable with that reported for diabetic peripheral neuropathy (6%-16%) 22,23 and postherpetic neuralgia (approximately 12%). 22 Therefore, patients with SCI do not seem more susceptible to developing peripheral edema in response to pregabalin than patients with other neuropathic pain conditions.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Treatment-emergent peripheral edema was reported in 13.4% of pregabalin-treated patients in this study, which is similar to the incidence reported in the previous trial of pregabalin for SCI (10%) 14 and comparable with that reported for diabetic peripheral neuropathy (6%-16%) 22,23 and postherpetic neuralgia (approximately 12%). 22 Therefore, patients with SCI do not seem more susceptible to developing peripheral edema in response to pregabalin than patients with other neuropathic pain conditions.…”
supporting
confidence: 90%
“…Indeed, somnolence occurred more frequently in the placebo arm (13%) in this study than what is reported for other placebo-controlled trials of pregabalin (2%-6%). 13,22,23 Overall, somnolence observed in this study was mostly mild in intensity (8 moderate and 1 severe case in pregabalin-treated patients) and discontinuations due to somnolence occurred in only 1.8% of patients receiving pregabalin.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…However, not all trials with pregabalin have been positive (15,86,95,96), especially when treating advanced refractory patients (93). Pregabalin, in contrast to gabapentin (see below), has a linear, dose-proportional absorption in the therapeutic dose range (150-600 mg/day) (88). In addition, pregabalin has a more rapid onset of action and more limited dosage range that requires minimal titration.…”
Section: Approved Medicationsmentioning
confidence: 99%
“…Recommendations from recent international and regional guidelines were reviewed in addition to discussion of recent systematic reviews, meta-analyses, and peer-reviewed randomised, double-blind, placebo-controlled studies; [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] a number of Cochrane reviews were also referred to. [31][32][33][34][35][36][37][38][39][40] The validity, clinical relevance, and applicability of the evidence for peripheral and central NeuP in South Africa were discussed.…”
Section: Evidence Evaluationmentioning
confidence: 99%